2018
DOI: 10.1002/ange.201809608
|View full text |Cite
|
Sign up to set email alerts
|

Selective C−N Borylation of Alkyl Amines Promoted by Lewis Base

Abstract: An efficient method for the metal-free deaminative borylation of alkylamines,u sing bis(catecholato)diboron as the boron source,todirectly synthesize various alkylpotassium trifluoroborate salts is introduced. The key to this high reactivity is the utilization of pyridinium salt activated alkylamines,with acatalytic amount of abipyridine-type Lewis base as ap romoter.T his transformation shows good functionalgroup compatibility (e.g., it is unimpeded by the presence of aketone,indole,internal alkene,orunactiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…Thereaction was shown to also proceed under thermal conditions,albeit in decreased yields.Asubsequent study uncovered that the borylation of N-alkyl pyridinium salt 1 could be efficiently enabled by aLewis base catalyst at elevated temperatures. [53] Therein, fragmentation of the diboron bond is facilitated by abipyridyl Lewis base to provide ahighly reducing pyridinestabilized boryl radical, which readily induces reductive fragmentation of 1 through SET.…”
Section: N-carbon-substituted Pyridinium Reagentsmentioning
confidence: 99%
“…Thereaction was shown to also proceed under thermal conditions,albeit in decreased yields.Asubsequent study uncovered that the borylation of N-alkyl pyridinium salt 1 could be efficiently enabled by aLewis base catalyst at elevated temperatures. [53] Therein, fragmentation of the diboron bond is facilitated by abipyridyl Lewis base to provide ahighly reducing pyridinestabilized boryl radical, which readily induces reductive fragmentation of 1 through SET.…”
Section: N-carbon-substituted Pyridinium Reagentsmentioning
confidence: 99%
“…6b ). A bathochromic shift of the mixture proves the strong evidence for the existence of an electron-donor-acceptor (EDA) complex 60 , 63 65 , 68 71 . Furthermore, using TEMPO or 1,1-diphenylethylene as radical scavengers in the reactions with visible light irradiation, trapped products 36 and 37 were detected and isolated (Fig.…”
Section: Discussionmentioning
confidence: 82%
“…Traditional methods to prepare them include electrophilic borylation of organolithium or Grignard reagents and hydroboration of olefins 46 . The recent state-of-the-art synthesis of these compounds has evolved to utilize bench-stable alkyl radical precursors, especially redox-active alkyl halides [47][48][49][50][51][52][53][54][55][56][57][58] , Nhydroxyphthalimide (NHPI) esters [59][60][61] , Katritzky salts [62][63][64][65] , xanthates/oxalates 66 , thionocarbonates 67 , and even alkanes 68 . Given the importance of alkylboronic esters, we explored the desulfurative borylation of thianthrenium salts under photo-and thermoinduced conditions (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a seminal work, Watson et al demonstrated that pyridinium salts, also known as "Katritzky salts" which are easily formed from primary amines and pyrylium salt, could be used as alkyl radical precursors in cross-coupling with arylboronic acids 27 . Since then, many elegant approaches based on the utilization of these redox active amines for deaminative functionalization such as arylation [28][29][30] , borylation 31,32 , alkenylation 33 , allylation 34 , alkyl-Heck-type reaction 35,36 , carbonylation 37 , alkylation [38][39][40][41] , di uoromethylation 42 and C-heteroatom bondforming reactions [43][44][45] have been established. However, the deaminative alkynylation of alkyl amines to form C(sp 3 )-C(sp) bond still remains elusive.…”
Section: Introductionmentioning
confidence: 99%